An Evaluation of Reading Materials in Indonesia Vocational English Textbook - Setiawan, Dimas Andi; Wahyuna, Yuna Tresna; Mobit, Mobit (Peneliti.net, 2024)
Textbooks are very influential for teachers and students in the learning process. This study aims to evaluate reading materials in textbooks. The researchers used an evaluation checklist framework developed by (Mohamed, 2013). The subject of this research is a textbook that uses an Merdeka curriculum. The result show that sufficient reading materials with a variety of texts is available in each chapter. Reading materials also helps students in reading comprehension. In addition to reading materials, it is also interesting and up-to-date by raising the latest issues. Then in terms of some reading, it is also easy with only a few paragraphs. In addition, the reading length corresponds to the textbook's grade level and uses several authentic materials. This means that this textbook is considered good in terms of reading materials. For the next research, can focus on other aspects such as speaking and listening materials.